Hypophosphatemic Rickets: A New Mutation - Maio, P (2018)
Introduction: Phosphopenic rickets is characterized by hypophosphatemia with hyperphosphaturia, normal calcemia and normal or mildly elevated PTH. This pathology may be caused by mutations in PHEX gene (phosphate regulating endopeptidase homolog X-linked). We present a clinical report of a girl with phosphopenic rickets, as consequence of a new mutation of PHEX gene. Clinical Case: We present a 4-year-old female, with unremarkable family history, who presented with failure to thrive since the first year of life (height at the 5th centile, and with the age of four below 5th centile). Blood tests showed hypophosphatemia (2.4 mg/dL), elevated alkaline phosphatase (495 U/L), normal calcemia, mildly elevated PTH (97.2 pg/mL; RR <68.3) and normal levels of 25(OH)D and 1.25(OH)D vitamins. The radiological study showed bone deformity of the radius and femur. Diagnosis of hypophosphatemic rickets was made and she was medicated with phosphorus and calcitriol. Currently, the patient has no clinical or radiographic signs of rickets, osseous age is according to real age and there was a considerable increase in growth rate (between 25th and 50th centiles). Renal ultrasound shows incipient signs of nephrocalcinosis since she was 9-year-old. The genetic study detected a heterozigous mutation of the PHEX gene: variant c.767_768del (p.Thr256Serfs*7). This variant is not described in the literature or databases. However, since it introduces a premature stop codon that can produce a truncated protein, this is very likely a pathogenic variant. The parent’s genetic study is still in progress. Conclusions: Presently more than 200 mutations in the PHEX gene have been found to cause hypophosphatemic rickets. We describe a new mutation of this gene. Knowledge about new mutations can improve patient’s outcome.